Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Use the Distributive Property to solve the equation. 4x - 2(x - 3) = -4 + 5x - 5

Sagot :

Answer:

x=5

Step-by-step explanation:

First, open up the parentheses to get 4x-2x+6=-4+5x-5. Now, move all numbers without variables to the right and those with variables to the left to get 4x-2x-5x=-4-5-6. Simplify both sides to have -3x=-15. Now divide both sides by -3 to get x=5